2016
DOI: 10.1136/bmjopen-2016-012580
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric fine particulate matter and breast cancer mortality: a population-based cohort study

Abstract: ObjectivesAtmospheric fine particulate matter (PM2.5) has multiple adverse effects on human health. Global atmospheric levels of PM2.5 increased by 0.55 μg/m3/year (2.1%/year) from 1998 through 2012. There is evidence of a causal relationship between atmospheric PM2.5 and breast cancer (BC) incidence, but few studies have investigated BC mortality and atmospheric PM2.5. We investigated BC mortality in relation to atmospheric PM2.5 levels among patients living in Varese Province, northern Italy.MethodsWe select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 24 publications
4
37
2
1
Order By: Relevance
“…Moreover, the significantly elevated concentrations of the heavy metals cadmium, copper, lead, zinc and chromium were found in the water-extracted PM 2.5 during building demolition. Long-term exposure to PM 2.5 in Italy has been associated with increased risk of death due to breast cancer (Tagliabue et al, 2016). Interestingly, the findings herein are consistent with the previous epidemiological observations of Italian women who live near incinerators, who have been found to have an elevated risk of breast cancer mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the significantly elevated concentrations of the heavy metals cadmium, copper, lead, zinc and chromium were found in the water-extracted PM 2.5 during building demolition. Long-term exposure to PM 2.5 in Italy has been associated with increased risk of death due to breast cancer (Tagliabue et al, 2016). Interestingly, the findings herein are consistent with the previous epidemiological observations of Italian women who live near incinerators, who have been found to have an elevated risk of breast cancer mortality.…”
Section: Discussionsupporting
confidence: 91%
“…In fact CVD is the second leading cause of morbidity and mortality in cancer survivors mainly because of treatment-induced cardio toxicity [32]. PM 10 also influences cardiovascular mortality [7,25] and cancer prognosis [34]. We found that ORs for A&E presentations for CVE were higher for cancer patients than other categories, highlighting cancer patient susceptibility to high PM 10 .…”
Section: Discussionmentioning
confidence: 76%
“…При долговременном действии РМ2,5 в зависимости от размера и химического состава могут возникать злокачественные новообразова-ния различной локализации [39][40][41].…”
Section: долговременное воздействие рмunclassified